IgE, IgG4 and IgA specific to Bet v 1‐related food allergens do not predict oral allergy syndrome. Issue 1 (30th November 2014) - Guhsl, E. E.; Hofstetter, G.; Lengger, N.; Hemmer, W.; Ebner, C.; Fröschl, R.; Bublin, M.; Lupinek, C.; Breiteneder, H.; Radauer, C.
Abstract Background Birch pollen‐associated plant food allergy is caused by Bet v 1‐specific IgE, but presence of cross‐reactive IgE to related allergens does not predict food allergy. The role of other immunoglobulin isotypes in the birch pollen‐plant food syndrome has not been investigated in detail. Methods Bet v 1‐sensitized birch pollen‐allergic patients (n = 35) were diagnosed for food allergy by standardized interviews, skin prick tests, prick‐to‐prick tests and ImmunoCAP. Concentrations of allergen‐specific IgE, IgG1, IgG4 and IgA to seven Bet v 1‐related food allergens were determined by ELISA. Results Bet v 1, Cor a 1, Mal d 1 and Pru p 1 bound IgE from all and IgG4 and IgA from the majority of sera. Immunoglobulins to Gly m 4, Vig r 1 and Api g 1.01 were detected in <65% of the sera. No significant correlation was observed between plant food allergy and increased or reduced levels of IgE, IgG1, IgG4 or IgA specific to most Bet v 1‐related allergens. Api g 1‐specific IgE was significantly (P = 0.01) elevated in celeriac‐allergic compared with celeriac‐tolerant patients. Likewise, frequencies of IgE (71% vs 15%; P = 0.01) and IgA (86% vs 38%; P = 0.04) binding to Api g 1.01 were increased. Conclusion Measurements of allergen‐specific immunoglobulins are not suitable for diagnosing Bet v 1‐mediated plant food allergy to hazelnut and Rosaceae fruits. In contrast, IgE and IgA to the distantly related allergen Api g 1 correlate with allergy to celeriac.